An austenitic stainless steel welded joint, a welded structure, and a base steel material, as well as a method for manufacturing an austenitic stainless steel welded joint.
Patent Information
- Application Number
- JP2020201606
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-04
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-12-04
AI Technical Summary
【0019】 本発明によれば耐水素脆化性に加え、耐高温割れ性と耐候性とに優れるオーステナイト系ステンレス鋼溶接継手を得ることができる。
Smart Images

Figure 0007636164000005 
Figure 0007636164000006 
Figure 0007636164000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel welded joint, a welded structure, and a base steel material, as well as a method for manufacturing an austenitic stainless steel welded joint. [Background technology]
[0002] In recent years, hydrogen energy has been attracting attention as a clean energy source that does not emit greenhouse gases such as carbon dioxide. However, when utilizing hydrogen energy, hydrogen production equipment and the like can suffer from the problem of material embrittlement caused by hydrogen gas, known as hydrogen embrittlement.
[0003] Therefore, various materials have been developed to suppress hydrogen embrittlement. For example, Patent Documents 1 and 2 disclose austenitic stainless steels that have been developed with an increased Mn content and improved resistance to hydrogen embrittlement.
[0004] Austenitic stainless steels used in such hydrogen-related technologies are welded and used as welded joints when manufactured into parts and components. In welded joints, the weld metal melts during welding and then solidifies, and performance degradation is likely to occur in the welded joints. Therefore, it is important to improve hydrogen embrittlement resistance even in the welded joint state. For this reason, Patent Documents 3 and 4 disclose austenitic stainless steel welded joints with improved hydrogen embrittlement resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-143227 A [Patent Document 2] JP 2019-143228 A [Patent Document 3] International Publication No. 2018 / 180788 [Patent Document 4] JP 2015-171729 A Summary of the Invention [Problem to be solved by the invention]
[0006] Meanwhile, welded joints of austenitic stainless steels are required to have not only hydrogen embrittlement resistance but also hot cracking resistance and weathering resistance. If the hot cracking resistance is poor, cracks and a decrease in ductility in the welded metal part are likely to occur after welding. Also, if the weathering resistance is poor, the parts are likely to deteriorate and have a reduced life as members and parts.
[0007] However, Patent Documents 3 and 4 make no mention of hot cracking resistance and weather resistance, and the austenitic stainless steel welded joints disclosed in Patent Documents 3 and 4 leave room for further improvement in the above-mentioned properties.
[0008] An object of the present invention is to solve the above problems and to provide an austenitic stainless steel welded joint that is excellent in hot cracking resistance and weather resistance in addition to hydrogen embrittlement resistance. [Means for solving the problem]
[0009] The present invention has been made to solve the above-mentioned problems, and its gist is the following austenitic stainless steel welded joint, welded structure, and base steel material, as well as a method for manufacturing an austenitic stainless steel welded joint.
[0010] (1) A welded joint having a base material and a weld metal part, The chemical composition of the weld metal part is, in mass%, C: 0.15% or less, Si: 1.0% or less, Mn: 8.0-10.0%, P:0.030% or less, S: 0.0030% or less, Cr: 15.0-18.0%, Ni: 7.0-9.0%, N: 0.15-0.35%, B: 0.0002~0.01%, Mg: 0.0001 to 0.01%, Al: 0.005-0.20%, Cu: less than 1.0% Mo: 3.0% or less O: 0.080% or less, Ca: 0.0005-0.01%, Nb: 0-1.0%, Ti: 0 to 1.0%, V: 0-1.0%, W: 0-2.0%, Zr: 0-1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0~0.10%, REM: 0~0.10%, The balance is Fe and impurities. An austenitic stainless steel welded joint, in which the f-value, calculated by the following formula (i), is greater than 29.5 and less than 36.0. f value=Ni+0.72Cr+0.88Mo+1.11Mn-0.27Si+12.93C+7.55N (i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
[0011] (2) The chemical composition is, in mass%, Nb: 0.01 to 1.0%, Ti: 0.01 to 1.0%, V: 0.01 to 1.0%, W: 0.001 to 2.0%, Zr: 0.01-1.0%, Co: 0.01-2.0%, Ga: 0.001 to 0.10%, Hf: 0.01 to 0.10%, and REM: 0.01~0.10%, The austenitic stainless steel welded joint according to (1) above, comprising one or more selected from the following:
[0012] (3) The chemical composition satisfies the following formula (ii): The austenitic stainless steel welded joint according to the above (1) or (2), wherein the ratio of the N content of the weld metal portion to the N content of the base metal satisfies the following formula (iii): 0.15≦N+20×O-Al (ii) 0.90≦N W / N M ≦2.00 (iii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. Each symbol in the above formula is defined as follows. N W : N content of weld metal (mass%) N M : N content of base material (mass%)
[0013] (4) An austenitic stainless steel welded joint according to any one of the above (1) to (3), which uses a thin steel plate.
[0014] (5) The austenitic stainless steel welded joint according to any one of (1) to (4) above, which is used in a hydrogen production device.
[0015] (6) A welded structure having the austenitic stainless steel welded joint according to any one of (1) to (5) above.
[0016] (7) A base steel material used for the austenitic stainless steel welded joint according to any one of (1) to (5) above, Chemical composition, in mass%, C: 0.15% or less, Si: 1.0% or less, Mn: 8.0-10.0%, P:0.030% or less, S: 0.0030% or less, Cr: 15.0-18.0%, Ni: 7.0-9.0%, N: 0.15-0.25%, B: 0.0002~0.01%, Mg: 0.0001 to 0.01%, Al: 0.005-0.20%, Cu: less than 1.0% Mo: 3.0% or less O: 0.005% or less, Ca: 0.0005-0.01%, Nb: 0-1.0%, Ti: 0 to 1.0%, V: 0-1.0%, W: 0-2.0%, Zr: 0-1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0~0.10%, REM: 0~0.10%, The balance is Fe and impurities, and is an austenitic stainless steel base material.
[0017] (8) A method for producing an austenitic stainless steel welded joint according to (3) above, A manufacturing method in which N2 gas or a gas containing N2 is used as the shielding gas.
[0018] (9) A method for producing an austenitic stainless steel welded joint according to (3) above, The shielding gas is classified into three types: torch gas, back gas, and after gas. The manufacturing method according to (8) above, wherein welding is performed using a gas containing, by volume percent, 1.0% or more of N2 as the torch gas. Effect of the Invention
[0019] According to the present invention, it is possible to obtain an austenitic stainless steel welded joint which is excellent in hot cracking resistance and weather resistance in addition to hydrogen embrittlement resistance. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a schematic diagram showing an I-groove in the embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing a Y groove in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present inventors have investigated the hydrogen embrittlement resistance, hot cracking resistance and weathering resistance of austenitic stainless steel welded joints and have obtained the following findings (a) to (c).
[0022] (a) When austenite phase with low stability is processed, austenite phase regions with high dislocation density and austenite phase regions with low dislocation density are formed. In the austenite phase regions with high dislocation density, the austenite phase transforms into processing-induced martensite and generates hydrogen embrittlement starting points. Therefore, it is desirable to adjust the stability of the austenite phase and suppress the increase in local dislocation density by controlling the f value, which is an index of the stability of the austenite phase, in the chemical composition of the weld metal part. This is because it is possible to suppress the formation of starting points for hydrogen embrittlement.
[0023] (b) Cu is effective in suppressing an increase in local dislocation density and forming a uniform austenite phase processed structure. Therefore, it is an effective element in suppressing hydrogen embrittlement. On the other hand, if Cu is contained in excess, it may reduce hot cracking resistance. Cu has a relatively low melting point, so the liquid phase tends to remain during the solidification process of the weld metal, inducing cracking.
[0024] Therefore, in order to improve hot cracking resistance while ensuring hydrogen embrittlement resistance, it is preferable to adjust the f-value to an appropriate range in the chemical composition of the weld metal part in order to increase the stability of the austenite phase while limiting the Cu content to a certain range. Specifically, it is preferable to adjust the Mn, Ni, and N contents to increase the f-value. Furthermore, in order to improve hot cracking resistance, it is effective to reduce P and S, which are likely to cause cracking. It is also preferable to contain small amounts of Al, Ca, B, and Mg to reduce the grain boundary segregation of low-melting point elements and suppress the occurrence of cracking.
[0025] (c) In order to ensure weather resistance, it is preferable to control the contents of Cr, Mo, and N in the weld metal within a predetermined range. Of Cr, Mo, and N, Cr and Mo are elements whose concentration changes between the base metal and the weld metal are extremely small, and adjusting the content of the base steel increases weather resistance. On the other hand, N is denitrified in the weld metal during melting, and the chemical composition of the base steel changes significantly. Therefore, in order to suppress denitrification during melting, it is preferable to adjust the type of shielding gas in addition to controlling the chemical composition of the weld metal.
[0026] Specifically, it is desirable to use N2 gas or a gas containing 1.0% or more of N2 gas as the torch gas among the shielding gases. Also, when welding is performed with a shielding gas that does not contain N2 gas, it is also effective to control the N, O, etc. content of the weld metal within an appropriate range to improve the penetration of the weld. These methods can suppress denitrification and make the N content of the weld metal relative to the N content of the base metal 0.90 or more.
[0027] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0028] 1. Welded joints The welded joint according to the present invention is a welded joint having a base material and a weld metal part. The base material is composed of an original material part that is not affected by welding heat, and a weld heat affected material part that is affected by welding heat. The original material part is not affected by welding heat, so it inherits the chemical composition, metal structure, and other properties from the base steel material that is the material of the welded joint. Therefore, the chemical composition, metal structure, and other properties of the original material part are the same as those of the base steel material. The weld heat affected material part is also a part of the base material, and although it is not melted, the metal structure has changed from that of the original material part due to welding heat. Therefore, the weld heat affected material part has a different metal structure compared to the base steel material, but is the same as the base steel material in terms of chemical composition. The weld metal part refers to a metal part that melts and solidifies during welding. The weld metal part and the weld heat affected material part are collectively called a weld part.
[0029] 1-1. Chemical composition of weld metal The reasons for limiting each element in the chemical composition of the weld metal part are as follows. In the following description, "%" for the content means "mass %." The chemical composition of the weld metal part is the average chemical composition of the entire weld metal part from which the oxide film has been removed.
[0030] C: 0.15% or less C is an element effective in stabilizing the austenite phase and also contributes to improving hydrogen embrittlement resistance. However, excessive C content promotes grain boundary precipitation of Cr-based carbides, reducing weather resistance, hot cracking resistance, and toughness. For this reason, the C content is set to 0.15% or less. The C content is preferably set to 0.10% or less, and more preferably set to 0.07% or less. On the other hand, in order to obtain the above effects, the C content is preferably set to 0.01% or more.
[0031] Si: 1.0% or less Silicon is an effective element for deoxidation and also contributes to improving hydrogen embrittlement resistance. However, excessive silicon content promotes the formation of intermetallic compounds such as σ phase, which reduces weather resistance, hot cracking resistance, and toughness. For this reason, the silicon content is set to 1.0% or less. The silicon content is preferably set to 0.7% or less. On the other hand, in order to obtain the above effects, the silicon content is preferably set to 0.3% or more.
[0032] Mn: 8.0-10.0% Mn is an element effective in stabilizing the austenite phase, and contributes to improving hydrogen embrittlement resistance. It also increases the solid solubility limit of N, and therefore indirectly contributes to saving on expensive Ni. For this reason, the Mn content is set to 8.0% or more. The Mn content is preferably set to 8.5% or more, and more preferably set to 9.0% or more. However, excessive Mn content promotes the formation of the ε phase, which is highly susceptible to hydrogen embrittlement, and instead reduces hydrogen embrittlement resistance. For this reason, the Mn content is set to 10.0% or less.
[0033] P:0.030% or less P is an element contained in steel as an impurity, but it may become concentrated in the final solidification process, lowering the melting point of steel and promoting hot cracking (solidification cracking). For this reason, the P content is set to 0.030% or less. From the viewpoint of improving hot cracking resistance, the P content is preferably set to 0.025% or less, and more preferably set to 0.015% or less. On the other hand, if the P content is excessively reduced, the manufacturing cost of the base steel material used for the welded joint increases, so the P content is preferably set to 0.005% or more.
[0034] S: 0.0030% or less S is an element contained in steel as an impurity, and like P, may promote hot cracking. For this reason, the S content is set to 0.0030% or less. The S content is preferably set to 0.0020% or less, and more preferably set to 0.0010% or less. However, excessive reduction of S increases the manufacturing cost of the base steel material. For this reason, the S content is preferably set to 0.0001% or more.
[0035] Cr: 15.0~18.0% Cr is an element that is contained in a certain amount in stainless steel, and has the effect of improving weather resistance. For this reason, the Cr content is set to 15.0% or more. However, Cr is a ferrite-forming element. Therefore, if Cr is contained in excess, it destabilizes the austenite phase and reduces hydrogen embrittlement resistance. It also reduces hot workability. For this reason, the Cr content is set to 18.0% or less. The Cr content is preferably set to 17.0% or less, and more preferably set to 16.0% or less.
[0036] Ni: 7.0~9.0% Ni, together with Mn, is an element necessary for ensuring hydrogen embrittlement resistance and hot cracking resistance. For this reason, the Ni content is set to 7.0% or more. However, excessive Ni content increases the manufacturing cost of the base metal. For this reason, the Ni content is set to 9.0% or less. The Ni content is preferably set to 8.5% or less, and more preferably set to 8.0% or less.
[0037] N: 0.15~0.35% Like Mn and Ni, N is an element that is effective in improving hydrogen embrittlement resistance and weather resistance. For this reason, the N content is set to 0.15% or more. However, excessive N content may cause internal defects such as blowholes, reducing hot cracking resistance. It also forms Cr nitrides, reducing weather resistance. For this reason, the N content is set to 0.35% or less. The N content is preferably set to 0.30% or less, and more preferably set to 0.20% or less.
[0038] B: 0.0002 to 0.01% B has the effect of strengthening grain boundaries, improving strength, and suppressing the occurrence of cracks. For this reason, the B content is set to 0.0002% or more. The B content is preferably set to 0.0003% or more. However, even if B is excessively contained, not only does the effect saturate, but it also promotes the precipitation of boron compounds (BN, BC, Cr2B) at grain boundaries, reducing hot cracking resistance. For this reason, the B content is set to 0.01% or less. The B content is preferably set to 0.006% or less, and more preferably set to 0.002% or less.
[0039] Mg: 0.0001 to 0.01% Mg is an element effective for deoxidization and has the effect of improving weldability. For this reason, the Mg content is set to 0.0001% or more. The Mg content is preferably set to 0.0003% or more. However, excessive Mg content reduces manufacturability, such as refining the base metal, and increases manufacturing costs. For this reason, the Mg content is set to 0.01% or less. The Mg content is preferably set to 0.006% or less, and more preferably set to 0.003% or less.
[0040] Al: 0.005 to 0.20% In addition to being an effective deoxidizing element, Al has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundaries. As a result, hot crack resistance and the like are improved and the occurrence of cracks is reduced. For this reason, the Al content is set to 0.005% or more. The Al content is preferably set to 0.010% or more. However, excessive Al content inhibits weld penetration and reduces weldability. For this reason, the Al content is set to 0.20% or less. The Al content is preferably set to 0.08% or less, and more preferably set to 0.06% or less.
[0041] Cu: Less than 1.0% Cu is an element that is mixed in from raw materials such as scrap, and is effective in stabilizing the austenite phase and improving hydrogen embrittlement resistance. On the other hand, Cu is a low melting point element that segregates at grain boundaries and promotes high-temperature cracking due to P and S, making cracks more likely to occur. For this reason, the Cu content is less than 1.0%. The Cu content is preferably 0.5% or less. However, excessive reduction of Cu leads to restrictions on the raw materials for melting the base steel material, and increases manufacturing costs. For this reason, the Cu content is preferably 0.01% or more.
[0042] Mo: 3.0% or less Mo is an element that is mixed in from raw materials such as scrap and is effective in improving weather resistance, but if it is contained in excess, it promotes the formation of δ-ferrite phase and reduces hydrogen embrittlement resistance. For this reason, the Mo content is set to 3.0% or less. The Mo content is preferably set to 2.0% or less. On the other hand, excessive reduction of Mo leads to restrictions on the melting raw materials of the base material, and increases manufacturing costs. For this reason, the Mo content is preferably set to 0.01% or more. Also, from the viewpoint of improving weather resistance, the Mo content is more preferably set to 0.50% or more, and even more preferably set to 1.0% or more.
[0043] O: 0.080% or less O is an element contained in steel as an impurity, and reduces the toughness of the weld metal. For this reason, the O content is set to 0.080% or less. The O content is preferably set to 0.010% or less, and more preferably set to 0.005% or less. However, excessive reduction of O inhibits penetration during welding, reducing weldability. For this reason, the O content is preferably set to 0.0005% or more.
[0044] Ca: 0.0005 to 0.01% Ca has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundary. As a result, the hot crack resistance is improved and the occurrence of cracks is reduced. For this reason, the Ca content is set to 0.0005% or more. The Ca content is preferably set to 0.0020% or more. However, if Ca is contained in excess, the hot workability is deteriorated due to the formation of inclusions, and cracks are more likely to occur. For this reason, the Ca content is preferably set to 0.01% or less.
[0045] In addition to the above elements, one or more elements selected from Nb, Ti, V, W, Zr, Co, Ga, Hf, and REM may be contained within the ranges shown below. The reasons for limiting each element will be explained.
[0046] Nb: 0-1.0% Nb has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. As a result, it suppresses the occurrence of cracks during welding. For this reason, it may be contained as necessary. However, if Nb is contained in excess, the solid solution N concentration decreases, leading to a decrease in weather resistance and a decrease in manufacturability and workability during hot rolling of the base steel. Therefore, the Nb content is set to 1.0% or less. The Nb content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.01% or more.
[0047] Ti: 0-1.0% Ti has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. As a result, Ti suppresses the occurrence of cracks during welding. For this reason, Ti may be contained as necessary. However, if Ti is contained in excess, the solid solution N concentration decreases, leading to a decrease in weather resistance and a decrease in manufacturability and workability during hot rolling of the base steel. Therefore, the Ti content is set to 1.0% or less. The Ti content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably set to 0.01% or more.
[0048] V: 0 to 1.0% V has the effect of improving strength by dissolving in steel or precipitating as carbonitrides. Therefore, it may be contained as necessary. However, if an excessive amount of V is contained, carbonitrides are formed in excess, and the manufacturability of the base steel during hot rolling decreases. Therefore, the V content is preferably 1.0% or less. On the other hand, in order to obtain the above effect, the V content is preferably 0.01% or more.
[0049] W: 0~2.0% W has the effect of improving strength and weather resistance. Therefore, it may be contained as necessary. However, if an excessive amount of W is contained, the manufacturing cost of the base steel increases, so the W content is set to 2.0% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.001% or more.
[0050] Zr: 0-1.0% Zr has a deoxidizing effect. It also has an effect of improving weather resistance. Therefore, it may be contained as necessary. However, if Zr is contained in excess, toughness and workability decrease. Therefore, the Zr content is set to 1.0% or less. The Zr content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effects, the Zr content is preferably set to 0.01% or more.
[0051] Co: 0-2.0% Co has the effect of improving corrosion resistance and stabilizing the austenite phase. Therefore, it may be contained as necessary. However, if an excessive amount of Co is contained, the manufacturing cost of the base steel increases. Therefore, the Co content is set to 2.0% or less. On the other hand, in order to obtain the above effects, the Co content is preferably set to 0.01% or more.
[0052] Ga: 0 to 0.10% Ga has the effect of improving hot workability. Therefore, it may be contained as necessary. However, excessive Ga content reduces manufacturability. Therefore, the Ga content is set to 0.10% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.001% or more.
[0053] Hf: 0~0.10% Hf has a deoxidizing effect and has the effect of improving weldability. Therefore, it may be contained as necessary. However, if an excessive amount of Hf is contained, manufacturability such as refining decreases. For this reason, the Hf content is set to 0.10% or less. On the other hand, in order to obtain the above effect, the Hf content is preferably set to 0.01% or more.
[0054] REM: 0~0.10% REM has a deoxidizing effect and has the effect of improving weldability. It also has the effect of improving corrosion resistance. For this reason, it may be contained as necessary. However, if REM is contained in excess, not only will the effect saturate, but manufacturability will decrease during refining, etc. For this reason, the REM content is set to 0.10% or less. On the other hand, in order to obtain the above effects, the REM content is preferably set to 0.01% or more.
[0055] REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.
[0056] In the chemical composition of the present invention, the balance is Fe and impurities. Here, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process during industrial production of austenitic stainless steel welded joints, and are permissible within a range that does not adversely affect the present invention.
[0057] f-Score In the austenitic stainless steel welded joint according to the present invention, the f-value calculated as follows is a requirement as an index representing the stability of the generated austenite phase. Specifically, the f-value calculated by the following formula (i) is greater than 29.5 and less than 36.0.
[0058] f value=Ni+0.72Cr+0.88Mo+1.11Mn-0.27Si+12.93C+7.55N (i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
[0059] Here, if the f-value is 29.5 or less, the stability of the austenite phase is low and the hydrogen embrittlement resistance of the weld metal part is reduced. For this reason, the f-value is set to be more than 29.5. However, if the f-value is 36.0 or more, the weldability is reduced due to the high alloying. In addition, the raw material cost increases and the manufacturability is also reduced. For this reason, the f-value is set to be less than 36.0. From the viewpoints of hydrogen embrittlement resistance, hot cracking resistance, and economic efficiency, the f-value is preferably set to be in the range of 30.0 to 35.0.
[0060] In the austenitic stainless steel welded joint according to the present invention, it is preferable that the chemical composition of the weld metal portion satisfies the following formula (ii). 0.15≦N+20×O-Al (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.
[0061] If the right-hand side value of formula (ii) is less than 0.15, it becomes difficult to satisfy formula (iii) described later, and it becomes difficult to improve weather resistance. Therefore, the right-hand side value of formula (ii) is preferably 0.15 or more, more preferably 0.17 or more, and even more preferably 0.19 or more. The upper limit of the right-hand side value of formula (ii) is usually about 1.95.
[0062] 1-2.Nitrogen concentration ratio In order to obtain good weather resistance, the austenitic stainless steel welded joint according to the present invention preferably has a ratio of the N content of the weld metal part to the N content of the base metal satisfying the following formula (iii). The reason for this is that during welding, N, which is effective in improving weather resistance, is lost and so-called denitrification is likely to occur, but by satisfying the following formula (iii), this denitrification can be suppressed and weather resistance can be maintained.
[0063] 0.90≦N W / N M ≦2.00 (iii) Each symbol in the above formula is defined as follows. N W : N content of weld metal (mass%) N M : N content of base material (mass%)
[0064] If the value in formula (iii), which is the ratio of the N content of the weld metal part to the N content of the base metal, is less than 0.90, denitrification occurs during welding, making it difficult to obtain good weather resistance. For this reason, the value in formula (iii) is preferably 0.90 or more. The value in formula (iii) is more preferably 1.00 or more, and even more preferably 1.10 or more. On the other hand, if the value in formula (iii) exceeds 2.00, internal defects such as blowholes are likely to occur in the weld metal part. For this reason, the value in formula (iii) is preferably 2.00 or less, more preferably 1.80 or less, and even more preferably 1.60 or less.
[0065] 1-3. Base material In the weld joint according to the present invention, the chemical composition of the base metal is not particularly limited, but for example, it is preferable to adjust the chemical composition of the base metal to the range shown below. The chemical composition of the base metal is, in mass %, C: 0.15% or less, Si: 1.0% or less, Mn: 8.0 to 10.0%, P: 0.030% or less, S: 0.0030% or less, Cr: 15.0 to 18.0%, Ni: 7.0 to 9.0%, N: 0.15 to 0.25%, B: 0.0002 to 0.01%, Mg: 0.0001 to 0.01%, Al: 0.005 to 0.20%, Cu: 0.0001 to 0.01%, and Cu: 0.005 to 0.20%. : less than 1.0%, Mo: 3.0% or less, O: 0.005% or less, Ca: 0.0005-0.01%, Nb: 0-1.0%, Ti: 0-1.0%, V: 0-1.0%, W: 0-2.0%, Zr: 0-1.0%, Co: 0-2.0%, Ga: 0-0.10%, Hf: 0-0.10%, REM: 0-0.10%, and the balance: Fe and impurities. The chemical composition of the base material is the same as that of the base steel material, which is the raw material. In the base material, the original part mainly has a structure similar to that of the base steel material formed by the austenite phase, but the heat-affected part is affected by the welding heat, so the metal structure changes from that of the base steel material.
[0066] 2.Applications The welded joint according to the present invention is preferably used in hydrogen-related equipment that requires hydrogen embrittlement resistance, such as hydrogen production equipment. The welded joint is preferably manufactured using a thin steel plate as the base steel material. The welded joint according to the present invention can also be used to manufacture a welded structure.
[0067] 3. Manufacturing method A preferred method for manufacturing the welded joint according to the present invention will be described. The welded joint according to the present invention can obtain the effects as long as it has the above-mentioned configuration regardless of the manufacturing method, but it has been confirmed that it can be manufactured, for example, by the following manufacturing method.
[0068] First, prepare the base steel material that will be the material for the weld joint. The chemical composition of the base steel is the same as that of the base metal, and is as follows: C: 0.15% or less, Si: 1.0% or less, Mn: 8.0-10.0%, P: 0.030% or less, S: 0.0030% or less, Cr: 15.0-18.0%, Ni: 7.0-9.0%, N: 0.15-0.25%, B: 0.0002-0.01%, Mg: 0.0001-0.01%, Al: 0.005-0.20%, Cu: 1. It is preferable that the austenitic stainless steel be one having the following composition: less than 0%, Mo: 3.0% or less, O: 0.005% or less, Ca: 0.0005 to 0.01%, Nb: 0 to 1.0%, Ti: 0 to 1.0%, V: 0 to 1.0%, W: 0 to 2.0%, Zr: 0 to 1.0%, Co: 0 to 2.0%, Ga: 0 to 0.10%, Hf: 0 to 0.10%, REM: 0 to 0.10%, and the balance: Fe and impurities.
[0069] In welding, a filler metal may be used as necessary. The chemical composition of the welded joint may be affected not only by the chemical composition of the base steel, but also by the chemical composition of the filler metal. For this reason, when a filler metal is used in welding, it is preferable to adjust the chemical composition of the filler metal so that it satisfies the chemical composition of the weld metal.
[0070] The shape of the austenitic stainless steel that becomes the base steel is not particularly limited, but is preferably, for example, a steel plate (thin steel plate or thick steel plate), a pipe, a bar, etc. The base steel may be processed to provide a groove in the base steel for welding. The groove shape is not particularly limited, but examples thereof include an I-shape, a Y-shape, a V-shape, an inverted trapezoid, and a U-shape. The thickness of the base steel is not particularly limited, but is usually in the range of 0.5 to 50.0 mm.
[0071] Next, the base steel is welded, and a filler metal is used as necessary to form a welded joint. The welding method is not particularly limited, but it is preferable to use gas tungsten arc welding (TIG welding). Other welding methods include shielded metal arc welding (SMAW), flux-cored wire arc welding (FCAW), gas metal arc welding (GMAW), submerged arc welding (SAW), etc.
[0072] The welding conditions are not particularly limited, but for example, the welding speed is preferably 10 to 200 cm / min. The current value is preferably 50 to 300 A. Furthermore, it is preferable to use a shielding gas during welding. Here, the shielding gas is a gas used to block the atmosphere during welding, and is classified into three types: torch gas, back gas, and after gas.
[0073] Torch gas is the gas emitted from the torch used during welding. Aftergas is a shielding gas used to protect the bead surface of the weld from the atmosphere when the torch gas alone is not enough to shield the bead surface of the weld. Backgas is a shielding gas used to protect the bead on the back side of the weld from the atmosphere.
[0074] Here, in the welded joint according to the present invention, it is preferable to use one or more shielding gases selected from N2 gas, Ar gas, and CO2 gas, and in particular, from the viewpoint of suppressing denitrification, it is preferable to use N2 gas or a gas containing N2 gas.
[0075] In addition, it is preferable to use N2 gas, or a mixed gas of N2 gas containing 1.0% or more of N2 by volume and Ar gas, a mixed gas of N2 gas containing 1.0% or more of N2 by volume and CO2 gas, or a mixed gas of N2 gas containing 1.0% or more of N2 by volume, Ar gas, and CO2 gas as the torch gas. It is most preferable to use N2 gas as the entire shielding gas. The flow rate of the shielding gas is not particularly limited, but is preferably in the range of 10 to 40 L / min. Other conditions may be set appropriately taking other conditions into consideration.
[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0077] Austenitic stainless steel base steels (A1 to A20) having the chemical composition shown in Table 1 were prepared. The thicknesses of these base steels were 1.2 mm, 2.5 mm, and 4.0 mm, respectively. For these base steels, TIG welding was performed under the welding conditions shown in Table 2 to produce welded joints. When welding, the 1.2 mm and 2.5 mm thick base steels were butted together with an I groove as shown in Figure 1, and the 4.0 mm thick base steel was butted together with a Y groove with a root surface of 1.5 mm as shown in Figure 2, and one pass welding was performed using a common alloy. The common alloy had the same composition as the base steel. The flow rates of the shielding gas were the same for all of them, with the torch gas at 10 L / min, the back gas at 15 L / min, and the after gas at 30 L / min. In addition, the tip angle was 40°, the torch angle was 90°, and the protruding length was 5.0 mm. The arc length was 1.0 mm for the I groove and 2.0 mm for the Y groove.
[0078] [Table 1]
[0079] [Table 2]
[0080] The chemical composition of the weld metal of the welded joint is as shown in Table 3, and each composition shown in Table 3 is the average chemical composition of the entire weld metal from which the oxide film has been removed. It is the average composition of the entire weld metal. In addition, in the welded joint, the chemical composition of the weld heat affected zone and the base material other than the weld metal was the same as that of the base steel. The obtained welded joint was evaluated for hydrogen embrittlement resistance, weather resistance, and hot cracking resistance.
[0081] [Table 3]
[0082] (Hydrogen embrittlement resistance) Hydrogen embrittlement resistance was measured by the following procedure. A tensile test piece with a parallel part of 4 mm width x 20 mm length and a welded part in the center was taken. Next, the tensile test piece was subjected to strain rate of 5×10 at room temperature in 70 MPa hydrogen and in air. -5 A slow strain rate tensile test (hereinafter, simply referred to as "SSRT test") was conducted at 10000 / s. In the evaluation of the SSRT test, the tensile breaking strength and the tensile breaking elongation were measured. The hydrogen embrittlement resistance was evaluated using the hydrogen embrittlement resistance evaluation value. The hydrogen embrittlement resistance evaluation value can be calculated based on the following formula.
[0083] Hydrogen embrittlement resistance evaluation value = {(tensile strength or elongation at break in 70 MPa hydrogen) / (tensile strength or elongation at break in 0.1 MPa nitrogen)} × 100 (%) (a) When the hydrogen embrittlement resistance evaluation value of the tensile breaking strength calculated from the above formula was 95% or more and the hydrogen embrittlement resistance evaluation value of the tensile breaking elongation was 80% or more, it was deemed to have good hydrogen embrittlement resistance and was marked with "O". On the other hand, when the hydrogen embrittlement resistance evaluation value was less than the above values, it was deemed to have poor hydrogen embrittlement resistance and was marked with "X".
[0084] (weather resistance) Weather resistance was evaluated by the JASO-CCT test in accordance with JASO M 610-92. The test specimens used were 50mm wide x 100mm long plates with a weld in the center. The surface to be evaluated was the front bead side, which was finished with wet polishing using No. 600 grit sandpaper. The test conditions were 5 mass% NaCl aqueous solution spray (35℃ / 2h), dry (60℃ / 4h), and wet (50℃ / 95%RH / 2h), which was a total of 8h per cycle, and the test was continued for up to 30 cycles. The JASO-CCT test was judged based on the rating number in accordance with JIS G 0595:2004.
[0085] Examples where the difference in rating numbers between the base material and the welded parts (welded metal parts and welded heat affected parts) was less than 1.0 were deemed to have high weather resistance and were marked with ◎, while examples where the difference was between 1 and less than 2 were deemed to have good weather resistance and were marked with ○. Examples where the difference was between 2 and less than 2.5 were deemed to have an acceptable decrease in weather resistance and were marked with △. Examples where the difference exceeded 2.5 were deemed to have clearly decreased weather resistance compared to the base steel and were marked with ×.
[0086] (High temperature crack resistance) The hot cracking resistance was evaluated by a V-bend test of the welded portion. In the V-bend test, the specimen was placed on a V-block so that the surface bead of the welded portion was the outer surface of the bend, the bending angle was 90°, and the bending radius was the same as the plate thickness of the base steel. The outer surface of the bent portion after the bending test was visually inspected for the presence or absence of cracks. When no cracks were visually observed on the outer surface of the bent test piece described above, it was marked as having hot cracking resistance, and a mark of ○ was recorded, and when cracks were observed, it was marked as having poor hot cracking resistance, and a mark of × was recorded. The results are summarized in Table 4 below.
[0087] [Table 4]
[0088] The welded joints B0 to B15, which satisfy the requirements of the present invention, were excellent in hydrogen embrittlement resistance, weather resistance, and hot cracking resistance. W / N M The value of N is less than 1.0, and the weather resistance is slightly inferior to other examples of the present invention. W / N M Since the requirements of formula (ii) and (iii) were not satisfied, the weather resistance was inferior to other examples of the present invention.
[0089] On the other hand, the welded joints B16 to B23, which do not satisfy the provisions of the present invention, were poor in at least one of hydrogen embrittlement resistance, weather resistance, and hot cracking resistance. B16 to B19 had poor weather resistance because any of C, N, Cr, Ti, and Nb related to weather resistance did not satisfy the provisions of the present invention. B20 had poor hydrogen embrittlement resistance because the f value was below the prescribed value, although the chemical composition of each element satisfied the provisions of the present invention. B16 and B21 to 23 had poor hot cracking resistance because any of C, P, S, Cu, Al, Ca, B, and Mg related to hot cracking resistance did not satisfy the provisions of the present invention.
Claims
1. A welded joint having a base material and a weld metal portion, The chemical composition of the weld metal part is, in mass%, C: 0.15% or less, Si: 1.0% or less, Mn: 8.0 to 10.0%, P: 0.030% or less, S: 0.0030% or less, Cr: 15.0-18.0%, Ni: 7.0-9.0%, N: 0.15-0.35%, B: 0.0002-0.01%, Mg: 0.0001-0.01%, Al: 0.005-0.20%, Cu: less than 1.0% Mo: 3.0% or less, O: 0.080% or less, Ca: 0.0005-0.01%, Nb: 0 to 1.0%, Ti: 0 to 1.0%, V: 0 to 1.0%, W: 0 to 2.0%, Zr: 0 to 1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0-0.10%, REM: 0-0.10%, The balance is Fe and impurities. An austenitic stainless steel welded joint, wherein the f-value calculated by the following formula (i) is greater than 29.5 and less than 36.
0. f value=Ni+0.72Cr+0.88Mo+1.11Mn-0.27Si+12.93C+7.55N...(i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.
2. The chemical composition, in mass%, Nb: 0.01-1.0%, Ti: 0.01 to 1.0%, V: 0.01-1.0%, W: 0.001-2.0%, Zr: 0.01 to 1.0%, Co: 0.01-2.0%, Ga: 0.001-0.10%, Hf: 0.01 to 0.10%, and REM: 0.01-0.10%, The austenitic stainless steel welded joint according to claim 1, comprising one or more selected from the following:
3. The chemical composition satisfies the following formula (ii):
3. The austenitic stainless steel welded joint according to claim 1, wherein the ratio of the N content of the weld metal portion to the N content of the base metal satisfies the following formula (iii): 0.15≦N+20×O-Al...(ii) ..0≦! W / : M ≦.... ・・・(iii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. Each symbol in the above formula is defined as follows. N W :N content of weld metal part (mass%) N M : N content of base material (mass%)
4. The austenitic stainless steel welded joint according to any one of claims 1 to 3, wherein a thin steel plate is used.
5. The austenitic stainless steel welded joint according to any one of claims 1 to 4, which is used in a hydrogen production device.
6. A welded structure having the austenitic stainless steel welded joint according to any one of claims 1 to 5.
7. A base steel material used for the austenitic stainless steel welded joint according to any one of claims 1 to 5, The chemical composition, in mass%, is C: 0.15% or less, Si: 1.0% or less, Mn: 8.0 to 10.0%, P: 0.030% or less, S: 0.0030% or less, Cr: 15.0-18.0%, Ni: 7.0-9.0%, N: 0.15-0.25%, B: 0.0002-0.01%, Mg: 0.0001-0.01%, Al: 0.005-0.20%, Cu: less than 1.0% Mo: 3.0% or less, O: 0.005% or less, Ca: 0.0005-0.01%, Nb: 0 to 1.0%, Ti: 0 to 1.0%, V: 0 to 1.0%, W: 0 to 2.0%, Zr: 0 to 1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0-0.10%, REM: 0-0.10%, The balance is Fe and impurities, and is an austenitic stainless steel base steel material.
8. A method for producing an austenitic stainless steel welded joint according to claim 3, comprising the steps of: Shielding gas: N 2 Gas or N 2 A manufacturing method using a gas containing
9. The shielding gas is classified into three types: torch gas, back gas, and after gas; The torch gas contains 1.0% or more N by volume. 2 The method according to claim 8, wherein the welding is carried out using a gas containing
Citation Information
Patent Citations
Gas shielded welding wire for austenitic stainless steel
JP1995314178A
AUSTENITIC HIGH Mn STAINLESS STEEL WELD JOINT FOR HIGH-PRESSURE HYDROGEN GAS AND LIQUID HYDROGEN AND METHOD OF PRODUCING THE SAME
JP2015171729A
Method of manufacturing welded joint
JP2016094660A
HIGH Mn AUSTENITIC STAINLESS STEEL
JP2019143227A
HIGH Mn AUSTENITIC STAINLESS STEEL AND MANUFACTURING METHOD THEREFOR
JP2019143228A